2017
DOI: 10.1080/13803395.2017.1349879
|View full text |Cite
|
Sign up to set email alerts
|

HIV-associated executive dysfunction in the era of modern antiretroviral therapy: A systematic review and meta-analysis

Abstract: Our results suggest that discrete domains of EF may be differentially affected by HIV infection and moderating demographic and clinical variables. These findings have implications for the development of targeted cognitive remediation strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
46
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(51 citation statements)
references
References 122 publications
(115 reference statements)
4
46
1
Order By: Relevance
“…The signi cant effect of HIV on the TMT-B/A ratio score, along with the signi cant effect of HIV on the Stroop Interference trial, point to a shared underlying cognitive process being impacted in the HIV population, namely cognitive exibility. This observed association between HIV status and cognitive exibility problems adds to the existing literature that has shown impairments in cognitive exibility on other neuropsychological assessments [12,47,48]. Our signi cant nding utilizing the B/A ratio highlights the need to utilize the TMT-B/A ratio score in future studies when investigating the TMT, as it can allow for a more sensitive measure of executive dysfunction.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The signi cant effect of HIV on the TMT-B/A ratio score, along with the signi cant effect of HIV on the Stroop Interference trial, point to a shared underlying cognitive process being impacted in the HIV population, namely cognitive exibility. This observed association between HIV status and cognitive exibility problems adds to the existing literature that has shown impairments in cognitive exibility on other neuropsychological assessments [12,47,48]. Our signi cant nding utilizing the B/A ratio highlights the need to utilize the TMT-B/A ratio score in future studies when investigating the TMT, as it can allow for a more sensitive measure of executive dysfunction.…”
Section: Discussionsupporting
confidence: 56%
“…There has been a lack of comparison between different executive functioning measures in individuals living with HIV who also have cocaine dependence. A recent systematic review and meta-analysis [12] pointed out the considerable differences within the conceptualization and measurement of executive functioning within the HIV population. Overall, there is a consensus that executive functioning impairments exist within both the HIV population and the cocaine dependence population.…”
Section: Introductionmentioning
confidence: 99%
“…The frontal/ACC (especially the ACC) receives rich dopaminergic innervation as part of the mesocortical pathway that originates from dopaminergic neurons in the ventral tegmental area (Nolan & Gaskill, ), and studies have suggested that the mesocortical dopamine fibers projection to the prefrontal cortex and ACC is important for executive function, working memory, motivation, and emotion [Nolan & Gaskill, ]. Here we hypothesized that the injury to the dopaminergic system in HIV (Chang et al, ; Kumar et al, ; Nath et al, ) might have contributed to the high prevalence of frontal/ACC atrophy, as well as executive dysfunction (Heaton et al, ) and apathy (Paul et al, ; Walker & Brown, ) in HIV+ adults. Future studies with multimodal neuroimaging techniques along with comprehensive neuropsychology tests are needed to test this hypothesis.…”
Section: Discussionmentioning
confidence: 94%
“…The hypothesis of early ACC dysfunction in HIV‐disease is also supported by the high prevalence of apathy in HIV (Paul et al, ; Walker & Brown, ), even in those with acute infection (Kamat et al, ). Neuropsychology studies (Cummings, ) have revealed a direct link between apathy and lesions to the ACC, suggesting the high prevalence of apathy in HIV might be associated with the highly prevalence of ACC injury.…”
Section: Discussionmentioning
confidence: 97%
“…Spatial learning, spatial memory, and working memory are three of seven cognitive ability criteria evaluated during neuropsychological (NP) diagnosis of mild NCI [ 6 ] and they are frequently affected in patients on HIV-suppressive ART (reviewed in [ 9 , 10 ]). The impairment of associative memory in infected mice shown in FC behavioral tests may be indicative of neuropsychiatric disorders also affecting HIV-positive individuals [ 111 114 ]. Although rodents and rodent behavioral tests do not fully reproduce the complexity of human behavior, our results indicate that murine HIV-NCI reflects some cognitive abnormalities seen in HIV-positive patients.…”
Section: Discussionmentioning
confidence: 99%